2018
DOI: 10.1530/ec-17-0380
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of GH, but not IGF1, in the hippocampus of the lactating dam after kainic acid injury

Abstract: Lactation embodies a natural model of morphological, neurochemical, and functional brain plasticity. In this reproductive stage, the hippocampus of the female is less sensitive to excitotoxins in contrast to nulliparity. Growth hormone (GH) and insulin-like growth factor 1 (IGF1) are known to be neuroprotective in several experimental models of brain lesion. Here, activation of the GH–IGF1 pituitary–brain axis following kainic acid (7.5 mg/kg i.p. KA) lesion was studied in lactating and nulliparous rats. Serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 56 publications
1
3
0
3
Order By: Relevance
“…Our results showed that this hormonal system increases its local expression in response to cell damage, mainly during reoxygenation, although it is important to note that GHR expression decreases in this condition, perhaps as a negative feedback mechanism. These results are consistent with the numerous evidence that indicates that the endogenous expression of GH and IGF-1 during a damaging condition, whether due to hypoxia [11,61], excitotoxicity [12,62], or trauma [13,63], plays a critical role within the mechanisms triggered by neurons to preserve their survival and viability.…”
Section: Discussionsupporting
confidence: 92%
“…Our results showed that this hormonal system increases its local expression in response to cell damage, mainly during reoxygenation, although it is important to note that GHR expression decreases in this condition, perhaps as a negative feedback mechanism. These results are consistent with the numerous evidence that indicates that the endogenous expression of GH and IGF-1 during a damaging condition, whether due to hypoxia [11,61], excitotoxicity [12,62], or trauma [13,63], plays a critical role within the mechanisms triggered by neurons to preserve their survival and viability.…”
Section: Discussionsupporting
confidence: 92%
“…The neuroprotective actions of GH in the hippocampus include prevention of excitotoxic cell death [ 106 ]. In lactating rats treated with kainic acid, hippocampal GH increased significantly, demonstrating a locally mediated neuroprotection mechanism [ 107 ]. It has been shown that damage due to oxidative stress, neurotoxicity, or hypoxic injury was reduced in GH-treated subjects, suggesting that this effect likely involves both local and systemic IGF-I actions [ 108 , 109 , 110 ].…”
Section: Expression and Neurotrophic Effects Of Growth Hormone (Ghmentioning
confidence: 99%
“…For the Gh , the primer used was developed by Dra. Maricela Luna [38]: Forward ; Reverse . The following pre-developed assays from Life Technologies were used: for rat Igf 1, the assay Rn00710306_m1, for Gapdh , which was used as a constitutive gene for Igf1 , the assay Rn01775763_g1.…”
Section: Methodsmentioning
confidence: 99%